2020
DOI: 10.1016/j.canlet.2020.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Combined administration of a small-molecule inhibitor of TRAF6 and Docetaxel reduces breast cancer skeletal metastasis and osteolysis

Abstract: A 2020, 'Combined administration of a small-molecule inhibitor of TRAF6 and Docetaxel reduces breast cancer skeletal metastasis and osteolysis: Running title : TRAF6/NFkB inhibition reduced breast cancer metastasis', Cancer letters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 93 publications
2
20
0
Order By: Relevance
“…We focused on the TRAF domain, which binds to the cytoplasmic tails of cell‐surface receptors. Inhibiting the protein interactions of this domain has been associated with decreased osteoclastogenesis, 37 increased insulin sensitivity, 38 and reduced breast cancer metastasis 39 . Structures of TRAF6 in complex with natural peptide ligands have revealed a conserved binding mode 40 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on the TRAF domain, which binds to the cytoplasmic tails of cell‐surface receptors. Inhibiting the protein interactions of this domain has been associated with decreased osteoclastogenesis, 37 increased insulin sensitivity, 38 and reduced breast cancer metastasis 39 . Structures of TRAF6 in complex with natural peptide ligands have revealed a conserved binding mode 40 …”
Section: Resultsmentioning
confidence: 99%
“…Inhibiting the protein interactions of this domain has been associated with decreased osteoclastogenesis, 37 increased insulin sensitivity, 38 and reduced breast cancer metastasis. 39 Structures of TRAF6 in complex with natural peptide ligands have revealed a conserved binding mode. 40 To obtain a structural model of TRAF6 alone, we removed the peptide ligand from the TRAF6-CD40 structure (PDB ID: 1LB6) and targeted a single, monomeric domain.…”
Section: Designing Peptide Binders Of Traf6mentioning
confidence: 99%
“…While little is known regarding the association of TRAF6 in breast cancer, it was found over-expressed in triple negative BC and it expression correlates with metastatic outcome [53]. In addition, a recent study reported that a molecule, an inhibitor of TRAF6, decreases metastasis in mouse BC models [54].…”
Section: Discussionmentioning
confidence: 99%
“…To increase the frequency of bone metastases and reduce the need for intra-cardiac injections, bone seeking sub-lines of MDA-MB-231 cells have been produced via repeated in vivo passaging through mouse bones [7,15,19,28] ; MDA-MB-231-B02, MDA-MB-231-B and MDA-MB-231-bone cells form tumours in up to 90% of mice following injection into the caudal artery, whereas MDA-IV cells form tumours in 80%-90% of mice after injection into the lateral tail vein [7,15,19,[28][29][30][31] . Via a similar mechanism, of in vivo passaging, researchers have also produced a bone seeking MCF7 breast cancer cell line that predominantly forms osteolytic lesions after 10-12 weeks [26] .…”
Section: Immortalised Breast Cancer Cell Linesmentioning
confidence: 99%